Stereodivergent Synthesis of Aldol Products Using Pseudo-C2 Symmetric N-benzyl-4-(trifluoromethyl)piperidine-2,6-dione - Rina Yada; Tomoko Kawasaki-Takasuka; Takashi Yamazaki (Molecules, 2024)
The present article describes the successful performance of crossed aldol reactions of the CF3-containing pseudo-C2 symmetric cyclic imide with various aldehydes. The utilization of HMPA as an additive attained the preferential formation of the anti-products in good to excellent yields, which contrasts with our previous method without this additive, proceeding to furnish the corresponding syn-isomers. The effective participation of ketones and α,β-unsaturated carbonyl compounds in reactions with this imide was also demonstrated to expand the application of this imide.